AB0050 Estrogen-Regulated STAT1 Activation Promotes TLR8 Overexpression and Facilitates Mirokine Signaling Via Exosomes Containing MIR-21 Endogenous Ligand: A Novel Innate Inflammatory Pathway in Systemic Lupus Erythematosus. (9th June 2015) - Young, N.A.; Wu, L.-C.; Amici, S.; Guerau, M.; Severin, M.; Lovett-Racke, A.; Valiente, G.; Burd, C.; Hampton, J.; Jarjour, W.
Abstract : Background: Recent studies suggest that innate immune responses may play a significant pathological role in systemic lupus erythematosus (SLE). TLR8 is an innate immune system receptor that stimulates inflammation by recognizing and binding to single-stranded viral RNA sequences, but recent work has shown that miR-21 can also act as an endogenous TLR8 ligand in carcinogenesis via exosomes. Previously, we demonstrated that estrogen can lower the threshold of immune cell activation and lead to enhanced TLR8 expression, especially in the presence of synthetic TLR8 agonist stimulation. Objectives: Our goal was to better characterize the estrogen-mediated signaling pathway in SLE leading to TLR8 up-regulation and to explore endogenous ligand stimulation. We hypothesized that estrogen stimulation of STAT1 could lead to transcriptional activation of TLR8, which could be stimulated by miR-21. Methods: Cells were treated with estrogen and collected for RT-PCR or Western blot analysis. ChIP-seq identified putative transcriptional binding sites following estrogen stimulation and EMSA confirmed DNA-protein complex formation with these sequences. STAT1 and estrogen receptor-α (ERα) expression were blocked by siRNA. Liposomal complexes containing fluorescently-labeled miR-21-Cy3 (red) were incubated in vitro ; cells were imaged in real time using fluorescent microscopy and TLR8 expression was measured by RT-PCR. Results: Estrogen stimulated STAT1 expression at the transcript level and enhanced phosphorylation of STAT1 was observed at the protein level in primary human cells and cell lines. CHiP-seq and EMSA analysis in cells stimulated with estrogen identified a putative response element for ERα to promote STAT1 expression and also confirmed STAT1-mediated transcriptional activation of TLR8. Using siRNA to target either ERα or STAT1, estrogen-medicated TLR8 induction was inhibited. To examine the role of endogenous ligand, miR-21 was detected in exosomes isolated from SLE serum and TLR8 expression was induced in vitro by stimulating cells with synthetically produced pseudoexosomes containing miR-21-Cy3. Conclusions: Therefore, similar to a cytokine or chemokine, exosome-encapsulated miR-21 can function as an inflammatory signaling molecule, or miRokine, by virtue of being an endogenous ligand for TLR8. Collectively, our data elucidates a novel innate inflammatory pathway in SLE by showing that estrogen-mediated expression of STAT1 promotes TLR8 expression, which can then be triggered by miR-21. Since this may significantly influence autoimmune inflammation, a future focus of this work will be to identify additional TLR agonists and to block exosomal miRokine signaling using antagomiR silencing. References: Fabbri, M., et al., MicroRNAs bind to Toll-like receptors to induce prometastatic inflammatory response. Proc Natl Acad Sci USA, 2012. 109(31): p. E2110-6. Young, N.A., et al., Estrogen modulation of endosome-associated toll-like receptor 8: an IFNalpha-independent mechanism of sex-bias in systemic lupus erythematosus. Clin Immunol, 2014. 151(1): p. 66-77. Acknowledgements: Funding was provided through the Wexner Medical Center at The Ohio State University. Disclosure of Interest: None declared